Robust monetary rules under unstructured and structured model uncertainty - Paul Levine; Joseph Pearlman (European Central Bank (ECB), 2008)
This paper compares two contrasting approaches to robust monetary policy design. The first developed by Hansen and Sargent (2003, 2007) assumes unstructured model uncertainty and uses a minimax robustness criterion to design monetary rules. This contrasts with an older literature that structures uncertainty by seeking rules that are robust across competing views of the economy. This paper carries out and compares robust design exercises using both approaches using a standard `canonical New Keynesian model'. We pay particular attention to a number of issues: First, we distinguish three possible forms of the implied game between malign nature and the policymaker in the Hansen-Sargent procedure. Second, in both approaches, we examine the consequences for robust rules of the zero lower bound (ZLB) constraint on the nominal interest rate, the monetary instrument. Finally, again for both types of robustness exercise we explore the implications of policy design when the policymaker is obliged to use simple Taylor-type interest rate rules.
Keywords: E52; E37; E58; 330; Robustness; structured and unstructured uncertainty; zero lower bound interest rate constraint; Geldpolitik; Regelbindung versus Diskretion; Zinspolitik; Entscheidung unter Risiko; Eurozone; Theorie; EU-Staaten